2022
DOI: 10.1155/2022/1703339
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Significance of Detection of Peripheral Blood VASP Level in Lung Cancer Patients

Abstract: This paper explores the relationship between the clinical value of vasodilator-stimulated phosphoprotein (VASP) in lung cancer tissue and its diagnosis and severity. Totally 100 patients who were clinically diagnosed with lung cancer from January 2018 to December 2020 were enrolled in our study. They were assigned into two groups according to the presence of lymph node metastasis. The VASP levels were measured by flow cytometry. The correlation between the expression of VASP in tumor tissue and the clinical ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%